Transcriptome analysis of Pacific white shrimp (Litopenaeus vannamei) challenged by Vibrio parahaemolyticus reveals unique immune-related genes. Issue 77 (June 2018) - Qin, Zhendong; Babu, V. Sarath; Wan, Quanyuan; Zhou, Meng; Liang, Risheng; Muhammad, Asim; Zhao, Lijuan; Li, Jun; Lan, Jiangfeng; Lin, Li
Abstract: Pacific white shrimp ( Litopenaeus vannamei ) is an important cultural species worldwide. However, Vibrio spp. infections have caused a great economic loss in Pacific white shrimp culture industry. The immune responses of Pacific white shrimp to the Vibrio spp. is not fully characterized. In this study, the transcriptomic profiles of L. vannamei hemocytes were explored by injecting with or without Vibrio parahaemolyticus . Totally, 42, 632 high-quality unigenes were obtained from RNAseq data. Comparative genome analysis showed 2258 differentially expressed genes (DEGs) following the Vibrio challenge, including 1017 up-regulated and 1241 down-regulated genes. Eight DEGs were randomly selected for further validation by quantitative real-time RT-PCR (qRT-PCR) and the results showed that are consistent with the RNA-seq data. Due to the lack of predictable adaptive immunity, shrimps rely on an innate immune system to defend themselves against invading microbes by recognizing and clearing them through humoral and cellular immune responses. Here we focused our studies on the humoral immunity, five genes (SR, MNK, CTL3, GILT, and ALFP) were selected from the transcriptomic data, which were significantly up-regulated by V. parahaemolyticus infection. These genes were widely expressed in six different tissues and were up-regulated by both Gram negative bacteria ( V. parahaemolyticus ) and Gram positive bacteria ( Staphylococcus aureus ). To further extend our studies, we knock-down those five genes by dsRNA in L. vannamei and analyzed the functions of specific genes against V. parahaemolyticus and S. aureus by bacterial clearance analysis. We found that the ability of L. vannamei was significantly reduced in bacterial clearance when treated with those specific dsRNA. These results indicate that those five genes play essential roles in antibacterial immunity and have its specific functions against different types of pathogens. The obtained data will shed a new light on the immunity of L. vannamei and pave a new way for fighting against the bacterial infection in Pacific white shrimp. Highlights: Transcriptomic database of Litopenaeus vannamei challenged with Vibrio parahaemolyticus. Provides valuable information about the five unique genes of L. vannamei to Vibrio infection. Gene knock-down studies exposed the importance and specificity of the five genes in shrimp immune system.